Cu-ZnO Embedded in a Polydopamine Shell for the Generation of Antibacterial Surgical Face Masks - Nicola d’Alessandro; Francesca Coccia; Luca Agostino Vitali; Giorgia Rastelli; Amedeo Cinosi; Andrea Mascitti; Lucia Tonucci (Molecules)
A new easy protocol to functionalize the middle layer of commercial surgical face masks (FMs) with Zn and Cu oxides is proposed in order to obtain antibacterial personal protective equipment. Zinc and copper oxides were synthesized embedded in a polydopamine (PDA) shell as potential antibacterial agents; they were analyzed by XRD and TEM, revealing, in all the cases, the formation of metal oxide nanoparticles (NPs). PDA is a natural polymer appreciated for its simple and rapid synthesis, biocompatibility, and high functionalization; it is used in this work as an organic matrix that, in addition to stabilizing NPs, also acts as a diluent in the functionalization step, decreasing the metal loading on the polypropylene (PP) surface. The functionalized middle layers of the FMs were characterized by SEM, XRD, FTIR, and TXRF and tested in their bacterial-growth-inhibiting effect against Klebsiella pneumoniae and Staphylococcus aureus. Among all functionalizing agents, Cu2O-doped-ZnO NPs enclosed in PDA shell, prepared by an ultrasound-assisted method, showed the best antibacterial effect, even at low metal loading, without changing the hydrophobicity of the FM. This approach offers a sustainable solution by prolonging FM lifespan and reducing material waste.